Synthesis, Characterization and Applications of Schiff Base Chemosensor for Determination of Cr(III) Ions - Khan, Sikandar; Muhammad, Mian; Algethami, Jari S.; Al-Saidi, Hamed M.; Almahri, Albandary; Hassanian, Athar Abdulfattah (Journal of fluorescence, 2022)
The development of a highly sensitive, selective, and efficient sensor for the determination and detection of Cr(III) ions remains a great challenge. Recently, some fluorescent chemosensors have been developed for the recognition of Cr(III) ions. But, the main drawbacks of the reported fluorescent chemosensors are the lack of selectivity and interference of anions and other trivalent cations. Herein, we designed and synthesized a novel thiazole-based fluorescent and colorimetric Schiff base chemosensor SB2 for the detection of Cr(III) ion by chemodosimetric approach. Using different analytical techniques including UV–vis, 13 C-NMR, 1 H-NMR, and FT-IR analysis the chemosensor SB2 was structurally characterized. The fully characterized chemosensor SB2 was used for the spectrofluorimetric and colorimetric detection of Cr(III) ions. Interestingly, chemosensor SB2 upon interaction with various metal cations including Ni 2+ , Na + , Cd 2+ , Ag + , Mn 2+ , K + , Zn 2+ , Cu 2+ , Hg 2+ , Co 2+ , Pb 2+ , Mg 2+ , Sn 2+ , Al 3+ and Cr 3+ displays highly selective and sensitive fluorescent (turn-on) and colorimetric (yellow to colorless) response toward Cr(III) ions. The fluorescence and UV–vis techniques confirmed the selective hydrolysis of azomethine group (-C = N-) of Schiff base chemosensor SB2 by Cr(III) ions. As a result, the fluorescence enhancement was observed that is corresponding to 2-hydroxy-1-nepthaldehyde (fluorophore). The chemosensor SB2 exhibits high interference performance towards Cr(III) ions over other metal cations in a wide pH range. Mover, the quite low detection limit was calculated to be 0.027 µg ml-1 (0.5 µM) (3σ/slop), lower than the maximum tolerable limits of Cr(III ions (10 µM) in drinking water permitted by the United States Environmental Protection Agency (EPA). These results show that chemosensor SB2 has great potential to detect selectively Cr(III) ions in the agricultural, environmental and biological analysis system. Graphical Abstract